Carbon cycle in advanced coal chemical engineering. (15th May 2015) - Yi, Qun; Li, Wenying; Feng, Jie; Xie, Kechang
Abstract : This review highlights possible routes, principle, and potential for the carbon cycle (CO2 ) in advanced coal chemical engineering. Abstract : This review summarizes how the carbon cycle occurs and how to reduce CO2 emissions in highly efficient carbon utilization from the most abundant carbon source, coal. Nowadays, more and more attention has been paid to CO2 emissions and its myriad of sources. Much research has been undertaken on fossil energy and renewable energy and current existing problems, challenges and opportunities in controlling and reducing CO2 emission with technologies of CO2 capture, utilization, and storage. The coal chemical industry is a crucial area in the (CO2 value chain) Carbon Cycle. The realization of clean and effective conversion of coal resources, improving the utilization and efficiency of resources, whilst reducing CO2 emissions is a key area for further development and investigation by the coal chemical industry. Under a weak carbon mitigation policy, the value and price of products from coal conversion are suggested in the carbon cycle.